The interaction between stock prices and interest rates in Turkey: Empirical evidence from ARDL bounds test cointegration - Turgut Tursoy (Financial Innovation, 2019)
This paper demonstrates a significant, long-running relationship between stock prices and domestic interest rates in Turkey's financial markets for the period of 2001 M1 - 2017 M4. Cointegration analysis is investigated using the autoregressive-distributed lag bounds (ARDL Bounds) test and vector autoregressive cointegration. Additionally, cointegrating equations such as the fully modified ordinary least square, dynamic ordinary least squares, and canonical cointegrating regression are applied to check the long-run elasticities in the concerned relationship. The ARDL Bounds and Johansen Cointegration test results show that, dynamically, both prices are significantly related to each other. The cointegrating equation outcomes demonstrate elasticities whereby both coefficients have negative signs. Additionally, the same results are corroborated by the impulse response where all variables respond negatively to each other.
Keywords: G11; G12; C22; 650; Stock price; Interest rates; Cointegration; ARDL; VAR